MUSIC AS A MEANS OF THERAPY FOR ELDERS - Van Harling, Jermias Hartes; Wibowo, Mungin Eddy; Ganap, Victor (Universitas Negeri Semarang, 2017)
Music no longer blends in the public space as simply a construction of sounds through elaborations of melody, rhythm, and harmony that adorn public spaces, but is now also used as a means of therapy to influence the listeners’ cognitive and emotional state. This study is meant to investigate the procedure of using music as a means of therapy and to examine the effect of music on elders’ emotional state and mood disorders. A mixed method approach was used, with a sequential exploratory design. This study used purposive sampling. Qualitative data was analyzed with psychoanalysis technique, while quantitative data was by t-test. The results show that the procedure of using music as a means of therapy for elders consist of three stages, i.e assessment, treatment, and evaluation and termination. The effect of music on the emotional state of elders was determined by three main factors, namely social-cultural factor, familiarity, and habits. The hypothesis test upon elders’ mood disorders revealed that music can reduce the quality of negative moods. A significant difference was found in the mean difference of the elders’ mood disorders before and after therapy, with a significant decrease in score from 107.36 to 51.9.